2017
DOI: 10.7206/jmba.ce.2450-7814.188
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Governance on the Performance of a Company. Some Empirical Findings from Indonesia

Abstract: Purpose: This study is aimed at analyzing the influence of the size of the board of directors, audit committee, institutional ownership and managerial ownership on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange. Methodology:The study analyses 156 Indonesia firms listed on the Indonesia Stock Exchange using linear regression analysis. Findings:The results indicated that the size of the board of directors has a positive effect on financial performance, while the size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 38 publications
(46 reference statements)
3
50
0
1
Order By: Relevance
“…Foreign investors have a positive impact and statistically significant effect on the performance of the listed company. Herdjiono and Sari (2017) indicated that the size of the board of directors has a positive effect on financial performance, while the size of the audit committee, institutional ownership and managerial ownership has no effect on the financial performance. While on the simultaneously testing, it showed that the size of the board of directors, audit committee size, institutional ownership and managerial ownership influence the financial performance Earnhart and Lizal (2006) analyzed the effects of ownership structure on corporate environmental performance and examines the relationship between financial performance and environmental performance in a transition economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Foreign investors have a positive impact and statistically significant effect on the performance of the listed company. Herdjiono and Sari (2017) indicated that the size of the board of directors has a positive effect on financial performance, while the size of the audit committee, institutional ownership and managerial ownership has no effect on the financial performance. While on the simultaneously testing, it showed that the size of the board of directors, audit committee size, institutional ownership and managerial ownership influence the financial performance Earnhart and Lizal (2006) analyzed the effects of ownership structure on corporate environmental performance and examines the relationship between financial performance and environmental performance in a transition economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies reported that the effectiveness of audit committees is to some extent dependent on the characteristics of the committee, such as its size (Dellaportas et al 2012;Herdjiono and Sari 2017). To be effective in controlling and monitoring managers' behaviour, the audit committee must have enough members to carry out its responsibilities (Vicknair et al 1993), with sufficient resources (Kalbers and Fogarty 1993).…”
Section: Audit Committee Sizementioning
confidence: 99%
“…Therefore, audit committees play an important role in overseeing and monitoring a company's management, with the aim of safeguarding the interests of the owners (Kallamu and Saat 2015). It is recognised that an effective audit committee focuses on enhancing company performance and competitiveness, particularly in a changing business environment which is beyond the control of the company (RamCharan 1998;Cravens and Wallace 2001;Herdjiono and Sari 2017). An effective audit committee is expected to emphasise optimisation of shareholders' wealth and prevent managers' maximisation of their personal interests (Wathne and Heide 2000;Bansal and Sharma 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The current study will use a percentage of independent commissioners compared to the total number of commissioners as independent commissioners' proxy (Widhianningrum & Amah, 2012). The current study will use the number of audit committees the company has as a measure of the audit committee (Herdjiono & Sari, 2017). The frequency of meetings of the board of commissioners is measured by the number of meetings of the board of commissioners held during the calendar year (Mardiyati, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The activities of the audit committee also show a significant relationship with the company's performance in a nonlinear manner (Sarpal, 2017). On the other hand, audit committee size is found to have no effect on financial performance (Herdjiono & Sari, 2017). Results from paper by Borlea et al (2017) concluded that having an audit committee to assist board activities does not necessarily imply significant performance improvements.…”
Section: Introductionmentioning
confidence: 99%